# algebra

posted by .

Solve the following rational expressions.
#1 (4y-3)/8 + (3)/(4y) = (y+3)/2
#2 5/(2x-1) = 1 - (8x-16)/(10x-5)

• algebra -

in each case find the LCD , then multiply each term by that.

I will do the #2
5/(2x-1) = 1 - (8x-16)/(10x-5)
5/(2x-1) = 1 - (8x-16)/(5(2x-1) )
LCD = 5(2x-1)

5/(2x-1)*5(2x-1) = 1*5(2x-1) - (8x-16)/(5(2x-1) )*5(2x-1)
25 = 10x - 5 - (8x-16)
14 = 2x
x = 7

## Similar Questions

1. ### math

•Post a response to the following: Take any number (except for 1). Square that number and then subtract one. Divide by one less than your original number. Now subtract your original number. Did you reached 1 for an answer?
2. ### algebra

Take any number (except for 1). Square that number and then subtract one. Divide by one less than your original number. Now subtract your original number. You reached 1 for an answer, didn’t you?
3. ### algebra 1

Simplify the rational expressions,if possible.State the excluded values,if any. 1.5x-5/10x^2-25x+15 2.w^2+6w+9/2w^2-18
4. ### algebra

Gina wrote this system of linear equations: 2x + y = 7 4x + 5y = 11 Which of the following shows the first four steps that Gina could have used to correctly solve this system for x?
5. ### Algebra

Factor quadratic expressions: 2x^2 + 9x + 4 10x^2 + 70x + 100 Solve quadratic equations by factoring: 2x^2 + 9x + 4 = 0 Solve by taking square roots: (x - 5)^2 - 81 = 0
6. ### Algebra 2

Can someone check my work please? I tried my best on all the problems but I still don't understand excluded values and how to simplify rational expressions. Thank you in advance for any help! 1)6x^5/2x^3 6/2 = 3 3x^5/x^3 x^5-x^3 =
7. ### Algebra

how do you solve this, its about rational expressions ?
8. ### Algebra 1 B Unit 6: Rational Expressions and Func

1. Solve. (-18x^3+17x+6)/(3x+2) A. -6x^2+4x+3 B. 6x^2+4x-3 C. -6x^2+4x-3 Dx^2-4x+3
9. ### Algebra

Combine the following rational expressions. 1/x-y-3/x^3-y^3=1/x-y-3/(x^2+xy+y^2)(x-y)
10. ### Algebra

Combine the following rational expressions. 1/x-y-3/x^3-y^3=1/x-y-3/(x^2+xy+y^2)(x-y)

More Similar Questions